IDENTIFIKASI POSTUR KERJA PROSES PEMBUATAN TAHU PADA PABRIK TAHU PAK UTAR DENGAN METODE REBA DAN OWAS - Nurfajriah Zhia; Santika Sari (Center for Study and Journal Management FTI UMI, 2020)
Pak Utar Tofu Factory is a conventional home industry which is engaged in the production of Tofu. There are three types of tofu produced, namely White Tofu, Chinese Tofu, and Jambi Tofu. In plain view, it can be seen that the work stations at this plant are still less ergonomic and have a very high risk of Musculoskeletal Disorders (MSDs) injury, therefore the authors conducted research by applying two methods namely Rapid Entire Body Assessment (REBA), and Ovako Working Analysis System (OWAS) for further comparison. Both methods have the viewpoint of the researcher, as well as the worker's perspective, and are used to examine each work station. After observation, there were 6 work stations with a total of 27 activities in total. After conducting research with these three methods, it was found that the REBA method resulted in all work stations having to be repaired, and the OWAS method resulting in all stations having to be improved. After reviewing and seeing the results of the two methods at each work station, the authors made improvements to the design of work tools at work station two because the work station did not have a major effect on the procedure of the work operator, compared to other work stations. The author makes a work tool repair plan at work station 1 which was originally dipped, into a water flush.